RFID Implementation and Enterprise Management in the Healthcare Sector - Erick C. Jones; Shalini Gupta; Latasha Starr (International Journal of Supply Chain Management, 2015)
Abstract- This article presents our method of applying radio frequency identification (RFID) technology within healthcare organizations, with the key concept of treating it as a supply chain enterprise. We present past research relating to the pertinent elements, including RFID, supply chain reference model (SCOR model), healthcare supply chains. We then present our methodology for evaluating the supply chain, understanding where to possibly implement RFID, evaluate how it would impact the enterprise metrics and processes, evaluate the return on investment (ROI) of these, evaluate the cross-dependency, choose areas to proceed forward with implementation, and finally begin implementation. Additionally, we present the results of a recent company where this was implemented. Keywords- Enterprise management, SCOR model, RFID, healthcare, hospital.